General Profile and Survival Probabilities of HIV Patients Registered at Anti-Retroviral Therapy Centre, New Civil Hospital, Surat, Gujarat - Ryavanki, Sridhar P; Kosambiya, J K; Mehta, Alap; Dayama, Sonal O; Solanki, Nitin; Kantharia, Shantilal L (National Journal of Community Medicine, 2013)
Introduction: With advent of Anti Retroviral Therapy (ART) life of HIV positive patients has prolonged. In pre ART era survival probability of HIV patients was well studied but very few studies are documented on survival probability of HIV patients on ART. The current paper is an attempt to describe general profile of adult HIV patients and provide an estimate of survival probabilities following the time of diagnosis and initiation of antiretroviral therapy and its relation with WHO staging and CD4 count. Methodology: Analysis of secondary data of ART centre, New Civil Hospital, Surat, Gujarat, India was carried in January 2011. Individuals with age >15 years and had required information for analysis were included. Death of HIV patient was considered as outcome. Descriptive statistics to describe general profile, Kaplan Meier Method for survival probability and Log rank test for significance was used. Cox's proportional hazards used to look for association between variables and survival. Results: The proportions of males were 66%. Age group 25-45years contributes 77% of cases. Majority of patients were married (75%). Survival probability after 15 years of diagnosis of HIV was 83%. The 4 year survival probability was 88% after the start of ART. The crude mortality rate was 8.6%. The mortality density was 10.8 per 1000 person years. The marital status and gender were not associated with survival. WHO clinical staging 3 and 4, CD4 count <200, and age >55 yrs have poor survival. There was significant difference in survival among different WHO clinical stages but no significant difference in survival between CD4 count 200 to 250, 250 to 350, 350 to 500 and >500. Conclusion: The new WHO guideline to start ART when CD4 count is <350 can cause financial burden to provide free ART without survival advantage.